Development of a Flipbook-Based Learning Module on the Concept of Simple Fractions in Grade IV Elementary School - Siti Agus Priyanti; Gingga Prananda; Gusnita Efrina; Rica Azwar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research was motivated by the difficulties experienced by students in understanding the concept of simple fractions, which are abstract in nature and often led to misconceptions. In addition, the learning module used by teachers was still limited to textbooks, making it less attractive to students. Therefore, this study aimed to develop a flipbook-based learning module on the topic of simple fractions for fourth grade elementary school students. The type of research used was Research and Development (R&D), and the development model applied was ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The product developed was a flipbook-based learning module. The results of the study showed that the module obtained an average score of 88.70% (very valid) from material, media, and language experts. The practicality test showed a score of 85.41% (very practical) based on teacher and student responses. The effectiveness test indicated an improvement in student learning outcomes with a mastery percentage above 80%. Thus, it was concluded that the flipbook-based learning module on the concept of simple fractions was feasible to be used in mathematics learning for fourth grade elementary school students.